Computational modelling of morphing reinforced composites - Jambulingam, Padmapooja (Nanyang Technological University, 2023)
Inspired by the art of nature, a flower shaped composite with petal-shaped edges was devised to investigate how geometry affects bistability of composite structures. Common geometries explored in academic studies often includes rectangular or square shapes. However, these geometries are not well-suited for applications requiring geometries to be more flexible, such as Soft Robotic Actuators. As such, to increase the versatility of bistable composites, flower shaped composites were designed. Geometrical changes includes varying the size of petals of the laminate and in-plane orientations to understand its effect on bistability. In this research, orientations of carbon fiber reinforcements used in epoxy polymer laminates were -45/45 and 0/90. These in-plane orientations are varied according to either local coordinate or global co-ordinate system. As the more commonly studied framework, the global co-ordinate system defines carbon fiber orientations for the entire structure, causing each petal of laminate to have varying orientation. However, local co-ordinate system abides an object-oriented framework, ensuring all the petals of the laminate have symmetrical fiber orientations. Apart from studying bistable shapes produced by the different fiber orientations, magnitudes and locations of the deformation of these laminates were explored. In addition, strain energies of these bistable structures were utilised to eliminate artificial stable shapes that might not exist experimentally. Results shows that generally in both local and global co-ordinate system, the number of stable shapes decreases with decreasing petal size for both 0/90 and -45/45 laminate stacking sequence. Both laminate stacking sequences in global co-ordinate system resulted in geometries with higher maximum deformation magnitudes as compared to their deformation changes in the local co-ordinate system.